2008
DOI: 10.1002/pd.1997
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome biochemical markers and screening for preeclampsia at first and second trimester: correlation with the week of onset and the severity

Abstract: Down syndrome biochemical markers levels are altered in those patients who subsequently developed preeclampsia and may be a useful screening test for preeclampsia. Inhibin-A is the most predictive marker and correlates with the severity of subsequent preeclampsia and inversely with the week of occurrence of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 37 publications
3
31
2
4
Order By: Relevance
“…Several other studies have also confirmed these finding [2,3,11]. However Kang, Wald and Davidson did not find any significant increase in AFP in those that developed pre-eclampsia compared to controls [15][16][17].…”
Section: Introductionsupporting
confidence: 67%
“…Several other studies have also confirmed these finding [2,3,11]. However Kang, Wald and Davidson did not find any significant increase in AFP in those that developed pre-eclampsia compared to controls [15][16][17].…”
Section: Introductionsupporting
confidence: 67%
“…The most effective thresholds were 2.0 multiples of the median (MoM) for alpha-fetoprotein (AFP) resulting in a positive likelihood ratio (LR) of 2.36 and a negative likelihood ratio of 0.96 [15]. On the other hand Davidson, Kang and Wald did not find any significant increase in MSAFP levels in preeclamptic women [8,16,17]. We found no significant difference in the rate of preeclampsia between the groups.…”
Section: Discussionmentioning
confidence: 57%
“…Inhibin A participates in the regulation of cell growth and differentiation in the placenta, and levels of maternal serum alpha-fetoprotein (MSAFP), maternal serum human chorionic gonadotrophin (hCG), and low uE 3 are associated with placental permeability and placentation. Despite many studies on the relationships between serum markers and preeclampsia, these markers have not achieved sufficient predictive value to be used alone for the screening of preeclampsia [7,8] .…”
Section: Introductionmentioning
confidence: 99%